2019
DOI: 10.1186/s12882-019-1365-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adolescents with chronic kidney disease who initiate haemodialysis treatment

Abstract: Background To describe the quality of life of adolescents initiating haemodialysis, to determine the factors associated with quality of life, and to assess coping strategies and their impact on quality of life. Methods All adolescents initiating haemodialysis between September 2013 and July 2015 in French paediatric haemodialysis centres were included. Quality of life data were collected using the “Vécu et Santé Perçue de l’Adolescent et l’Enfant” questionnaire, and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 40 publications
5
44
0
7
Order By: Relevance
“…Further studies have shown considerable growth in the number of CKD patients in Iran, as the number of these patients increases by 15% every year [12]. Currently, HD is the most common method of treatment for ESRD patients [13]. However, patients receiving HD have to deal with several issues and changes in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have shown considerable growth in the number of CKD patients in Iran, as the number of these patients increases by 15% every year [12]. Currently, HD is the most common method of treatment for ESRD patients [13]. However, patients receiving HD have to deal with several issues and changes in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Patients have various potential co-morbidities including limb pain. Limb pain may be associated with burning sensation, or itching, and in one study, 91% patients suffered from this [94]. This study shows association between insomnia and limb pain in dialysis patients and how areas surrounding renal nursing could be more involved for adult patients.…”
Section: Nursingmentioning
confidence: 64%
“…Several studies in the literature have reported a poorer quality of life in adolescents with CKD than in healthy adolescents (Dotis et al, 2016; Francis et al, 2018; Heath et al, 2017; Jesky et al, 2016; Maxwell et al, 2010; Moreira et al, 2015). Adolescents with CKD are required to make frequent hospital visits, and to comply with medication, dietary restrictions, and dialysis (Kelly 2016; Neul et al, 2013; Tjaden et al, 2017), and to obey many restrictions in their daily life activities (Baum, 2010; Clavé et al, 2019; Varni et al, 2007). Such adolescents have distinctively negative experiences in several domains related to their disease, treatment, and personal lives (Lin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%